The Filarial Dance Sign: A Distinctive Sonographic Marker of Scrotal Filariasis in Endemic Settings - Davra, Sanket Vinubhai; Pushkar, Kumar (Journal of Neonatal Surgery, 2025)
Background: Scrotal filariasis is an uncommon manifestation of lymphatic filariasis (LF), typically seen in endemic regions. While chronic presentations like hydrocele are well recognized, acute involvement of the spermatic cord is often overlooked. High-resolution ultrasonography (HRUS) aids diagnosis, particularly when the characteristic filarial dance sign (FDS) is present. Case Presentation: A 22-year-old male from an endemic area presented with right scrotal swelling and low-grade fever. HRUS revealed dilated, avascular lymphatic channels in the right spermatic cord with mobile echogenic structures showing swirling motion—consistent with FDS. The testis and epididymis were normal. Management: The patient received a 12-day course of Diethylcarbamazine, with marked symptomatic and sonographic improvement. Conclusion: FDS on ultrasound is a reliable, non-invasive marker of scrotal filariasis in endemic areas. Early recognition enables timely medical management and prevents unnecessary surgical intervention